Answer:
g = 61.
Step-by-step explanation:
g + 9 = 70 Subtract 9 from both sides of the equation:
g + 9 - 9 = 70 - 9
g = 61.
10 & 12
x = 1st consecutive even number
x + 2 = 2nd consecutive even number
x + x + 2 = 22
2x + 2 = 22
2x = 20
x = 10
x + 2 = 12
10 and 12 are the two consecutive even numbers
Answer:
57, 53, 49, 45
Step-by-step explanation:
Substitute for the n for n=1,2,3,4 so the first term is 57-4(1-1) so =57-4(0) so
a(1) = 57-0 = 57 so that is the 1st term
2nd term 57-4(2-1) so =57-4(1) so a(2) = 57-4 = 53, etc.
Answer:
91
Step-by-step explanation:
Multiplication first, so 7x4 = 28
28+63=91